A Critical Review on the Book New Left Thinkers - Tayebe Domanlou (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The New Left Thinkers is undoubtedly one of the most controversial and newsworthy works of the late English philosopher, Roger Scruton, which has been published in recent decades as a critique of the new left thinkers. Scruton analyzed, and critiqued the most important contemporary philosophers in the last decades, aimed to decrypt the new speak of the left discourse. The most common aspect between these thinkers, more than anything else, is the distance from the right discourse. By critical reading, Scruton tried to simplify the idea, complex language, and complicated theories of the New Left. He wanted to show how these ideas were emerged in emotional reaction to the historical events of their time, and actually they were rooted in the human’s need for faith and belief in something. Although criticizing the mainstream of Scruton’s time is a courageous subject, special and scares, and we can admire Scruton for doing this, in final analysis of this work, I must say Scruton argued and criticized the new left in a way that he should be criticized too. In the other word we can criticize Scruton as the same point that he criticized and accused the new left. Regardless of the content of his arguments, as the methodological view, his approach to these texts is selective, unscientific and emotional. By critical reviewing of this book, I try to prove my claim about the selective and emotional approach of Scruton in this article. Without arguing the content of his discussions, as far as possible, I show that the value-based approach and believing in single truth, and anger and hated of the Left and the New Left are the basis of his argument in criticizing the personality of thinkers, selecting and describing their theory and finally Seizure as he desired the argument. He argued in the same way and the same style that he claimed the New Left did it.